2018
DOI: 10.1038/s41390-018-0205-7
|View full text |Cite
|
Sign up to set email alerts
|

Changes in neuroplasticity following early-life social adversities: the possible role of brain-derived neurotrophic factor

Abstract: Social adversities experienced in childhood can have a profound impact on the developing brain, leading to the emergence of psychopathologies in adulthood. Despite the burden this places on both the individual and society, the neurobiological aspects mediating this transition remain unclear. Recent advances in preclinical and clinical research have begun examining neuroplasticity-the nervous system's ability to form adaptive changes in response to new experience-in the context of early-life vulnerability to so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 154 publications
(201 reference statements)
0
17
0
1
Order By: Relevance
“…A handful of studies have found smaller volumes among lower‐SES youth (Hanson et al, ; Luby et al, ; McDermott et al, ), but most do not, and it remains unclear what accounts for the differences. As with the hippocampus, discussed in the following section, BDNF could account for the positive associations between SES and amygdala curvature in males as abnormalities in BDNF methylation and mRNA expression in the amygdala are associated with early life adversity (Miskolczi et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A handful of studies have found smaller volumes among lower‐SES youth (Hanson et al, ; Luby et al, ; McDermott et al, ), but most do not, and it remains unclear what accounts for the differences. As with the hippocampus, discussed in the following section, BDNF could account for the positive associations between SES and amygdala curvature in males as abnormalities in BDNF methylation and mRNA expression in the amygdala are associated with early life adversity (Miskolczi et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Regions that are important for the regulation of social behavior, including subcortical regions such as the hippocampus, basal ganglia, and amygdala, undergo protracted development which renders them vulnerable to experience-dependent changes influenced by the environment for prolonged time periods (Miskolczi, Halasz, & Mikics, 2019). These time epochs of adaptive and dynamic brain changes are known as sensitive periods, and are regulated in part by brain-derived neurotrophic factor (BDNF; Miskolczi et al, 2019). BDNF reaches peak levels in adolescence and is involved in regulation of programmed cell death, synaptic pruning, and axonal and dendritic branching of rapidly proliferating and differentiating neurons (Yang et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Preclinical signs of dementia, for example may impact on the brain measures and may lead to earlier or accelerated decline although cognition is still normal (Costafreda et al., ; Gaser, Franke, Klöppel, Koutsouleris, & Sauer, ). Stress or unfavourable genetic configurations (e.g., genes coding pathologies like Huntington's disease or Down syndrome) may be other factors in determining brain structural decline (Bhatt et al., ; Mattson, Chan, & Duan, ; Miskolczi, Halász, & Mikics, ). Most important, however, is the possibility that the usage and non‐usage of specific psychological and motor functions have an influence on brain size.…”
Section: Discussionmentioning
confidence: 99%